2D‐Berry‐Curvature‐Driven Large Anomalous Hall Effect in Layered Topological Nodal‐Line MnAlGe. Issue 21 (18th March 2021) - Guin, Satya N.; Xu, Qiunan; Kumar, Nitesh; Kung, Hsiang‐Hsi; Dufresne, Sydney; Le, Congcong; Vir, Praveen; Michiardi, Matteo; Pedersen, Tor; Gorovikov, Sergey; Zhdanovich, Sergey; Manna, Kaustuv; et al.
Abstract: Topological magnets comprising 2D magnetic layers with Curie temperatures ( T C ) exceeding room temperature are key for dissipationless quantum transport devices. However, the identification of a material with 2D ferromagnetic planes that exhibits an out‐of‐plane‐magnetization remains a challenge. This study reports a ferromagnetic, topological, nodal‐line, and semimetal MnAlGe composed of square‐net Mn layers that are separated by nonmagnetic Al–Ge spacers. The 2D ferromagnetic Mn layers exhibit an out‐of‐plane magnetization below T C  ≈ 503 K. Density functional calculations demonstrate that 2D arrays of Mn atoms control the electrical, magnetic, and therefore topological properties in MnAlGe. The unique 2D distribution of the Berry curvature resembles the 2D Fermi surface of the bands that form the topological nodal line near the Fermi energy. A large anomalous Hall conductivity of ≈700 S cm –1 is obtained at 2 K and related to this nodal‐line‐induced 2D Berry curvature distribution. The high transition temperature, large anisotropic out‐of‐plane magnetism, and natural heterostructure‐type atomic arrangements consisting of magnetic Mn and nonmagnetic Al/Ge elements render nodal‐line MnAlGe one of the few, unique, and layered topological ferromagnets that have ever been observed. Abstract : A layered topological nodal‐line magnet MnAlGe is reported. The material exhibits a large anomalous Hall conductivity driven by the unique 2D Berry curvature distribution. The search for new layered topological magnets and exploration of magnetism and topological properties are enabled by this work.